Analisis faktor kecelakaan kerja pada proses pelayanan pipa dan meter dengan menggunakan metode Fault Tree Analysis (FTA) dan Failure Mode And Effect Analisis (FMEA) - Rozi, Fachrur; Sari, Rizqi Novita (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
Occupational safety and health (OSH) is an initiative to prevent occupational diseases and accidents. Especially in the warehousing section, the risk of work accidents very prone to happen. Company X’s pipe and meter warehouse is a storage and service area for goods such as pipes and meters. However, in the process of supplying and servicing work accidents are likely to occur. So to overcome the risk of work accidents, mitigation efforts are needed by applying the FMEA and FTA methods to assess the level of risk and how to prevent it. The results of calculations using the FMEA method in the preparation stage pipe service are eye irritation with an RPN value of 108, and at the implementation stage is cut by sharp material with an RPN of 432. Then in the service meter the results of the FMEA calculation, namely at the preparation stage is the foot injury with an RPN value of 24, then in the implementation of the work is the hand injury with an RPN obtained of 60. And in the FTA method the causes of work accidents include human error, material, method, and machine.